(untitled) (Plant Tissue Culture and Biotechnology, 2026)
An in vitro micropropagation protocol for cassava Manihot esculenta was developed through callus culture. The present investigation the highest callus induction was achieved on MS medium containing 8.0 mg/l 2,4-D. Inter node and leaf derived calli were transferred to MS medium supplemented with BAP and NAA for shoot regeneration. In this case 10.0 mg/l BAP alone produced highest number of shoots (4.8 ± 0.3) per explant having average length of 1.72 ± 0.2 cm. The combination of 10.0 mg/l BAP and 0.5 mg/l NAA further enhanced shoot proliferation, producing an average of 5.6 ± 0.6 shoots per explant with a mean shoot length of 3.6 ± 0.2 cm with a regeneration rate of 87%. Moderate BAP concentrations (4.0-10.0 mg/l) were optimal for indirect shoot regeneration, whereas NAA or Kn alone exhibited limited effects. Root induction was most effective on half-strength MS medium supplemented with 2.0 mg/l IBA, which resulted in 100% rooting, with the highest mean root number of 4.8 and root length of 2.8 cm. The regenerated plantlets were successfully acclimatized in pots containing a 1 : 1 mixture of cocopeat and autoclaved soil, exhibiting high survival rates under shade house conditions. Plant Tissue Cult. & Biotech. 35(2): 285-295, 2025 (December)